Safety Management Systems and Safety Culture in Aircraft Maintenance Organisations - Corrigan, Siobhan (My University, 2000)
A self-regulatory model was proposed to examine how different organisations manage safety, with particular emphasis on the human and organisational aspects. The relationships of different aspects of safety culture and safety management systems were explored through the deployment of different research measures and methods. Studies of four aircraft maintenance organisations included analysis of documentation and qualitative interviews, surveys of safety climate and attitudes, expected response to incidents and compliance with task procedures. The model was effective in analysing the salient features of each organisation' s safety management system, though it underestimated the roles of planning and change. The data from management interviews, the incidents survey and safety climate survey exhibited a large measure of agreement in differentiating between the different safety management systems and safety climate of the four organisations. The measures of compliance with task procedures and safety attitudes did not differentiate between the four organisations (though one organisation did differ from the others in safety attitudes). This suggests a strong, relatively homogeneous professional sub-culture of aircraft technicians spanning the different organisations. Differences in safety attitudes and climate were found between occupational groups, though in the case of climate the differences between occupational groups were a function of the organisation, suggesting a differentiated notion of safety culture. The professional sub-culture of technicians is likely to mediate between the organisation' s safety management system and safety outcomes.
PUBLISHED
Keywords: Safety management systems, Safety culture, Aircraft maintenance organisations; Identities in Transformation; Inclusive Society; Other; Employment